Photodegradation of methyl orange by using nanostructured coupled semiconductor photocatalyst (NCSP) - Nur Maisarah Shamsudin, 1988-; Halimaton Hamdan, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010